Effects of a 4-Step Standard Operating Procedure for the Treatment of Fever in Patients With Acute Stroke - Lee, Hanna; Hedtmann, Günter; Schwab, Stefan; Kollmar, Rainer (Frontiers in Neurology, 2021)
Background and Purpose: Fever in the acute phase of stroke leads to an unfavorable clinical outcome and increased mortality. However, no specific form of effective fever treatment has been established, so far. We analyzed the effectiveness of our in-house standard operating procedure (SOP) of fever treatment. Methods: This SOP was analyzed for a period of 33 weeks. Patients with cerebral ischemia (ischemic stroke, transient ischemic attack) or cerebral hemorrhage (intracerebral, subarachnoid) and body temperature elevation of ≥ 37.5 ° C within the first 6 days after admission were eligible for inclusion in the analysis. The results of SOP group, who´s data have been collected prospectively were then compared with a historical control group that had been treated conventionally 1 year earlier in the same period. The data of control group have been collected in retrospect. The primary endpoint was the total duration of the fever for the first 6 days after admission to the stroke unit. Results: A total of 130 patients (mean age of 78 ± 12) received 370 antipyretic interventions. Sequential application of paracetamol (n = 245), metamizole (n = 53) and calf compress (n = 15) led to significant reduction in body temperature. In patients who did not respond to these applications, normothermia could be achieved after infusion of the cooled saline solution. Normothermia could be achieved within 120 minutes in more than 90% of the cases treated by the SOP. The SOP reduced the fever duration in the 6 days significantly, from 12.2 ± 2.7 hours (95% confidence interval (CI) for mean) in the control group to 3.9 ± 1.0 hours (95% CI) in the SOP group (p < 0.001). The SOP was rated to be reasonable and effective. Conclusion: Our in-house SOP is cost-efficient and effective for fever treatment in stroke patients, that can be implemented by local health care professionals.